2019
DOI: 10.1101/810655
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Network dynamics underlying OFF responses in the auditory cortex

Abstract: Across sensory systems, complex spatio-temporal patterns of neural activity arise following the onset (ON) and offset (OFF) of simple stimuli. While ON responses have been widely studied, the mechanisms generating OFF responses in cortical areas have so far not been fully elucidated. Recent studies have argued that OFF responses reflect strongly transient sensory coding at the population level, suggesting they may be generated by a collective, network mechanism. We examine here the hypothesis that OFF response… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 110 publications
(143 reference statements)
0
8
0
Order By: Relevance
“…Directly computing the subspace angles between did not affect our conclusions (Supplement: Computation of subspace angles). Subspace angles have been used in [41] to show that OFF responses in auditory cortex to different stimuli lie mostly in orthogonal subspaces.…”
Section: Methodsmentioning
confidence: 99%
“…Directly computing the subspace angles between did not affect our conclusions (Supplement: Computation of subspace angles). Subspace angles have been used in [41] to show that OFF responses in auditory cortex to different stimuli lie mostly in orthogonal subspaces.…”
Section: Methodsmentioning
confidence: 99%
“…In a typical linear dynamical system, responses will decay away monotonically in the absence of a stimulus, making them poor candidates for coding with transients. Building on ideas from a class of linear systems called “non‐normal,” Bondanelli presented a framework for encoding multiple stimuli in strongly amplified transient trajectories by choosing the connectivity matrix to be the sum of appropriate low‐rank pieces (Bondanelli & Ostojic, 2020), and showed that it could explain various observed features of auditory cortical neural data, such as non‐monotonic transient activity at stimulus offset and better discriminability during the offset transient phase (Bondanelli, Deneux, Bathellier, & Ostojic, 2019).…”
Section: Sequences: a General Motif For Dynamic Neural Computationmentioning
confidence: 99%
“…To understand how EPI scales in comparison to existing techniques, we consider recurrent neural networks (RNNs). Transient amplification is a hallmark of neural activity throughout cortex, and is often thought to be intrinsically generated by recurrent connectivity in the responding cortical area [43][44][45]. It has been shown that to generate such amplified, yet stabilized responses, the connectivity of RNNs must be non-normal [43,50], and satisfy additional constraints [51].…”
Section: Scaling Inference Of Recurrent Neural Network Connectivity With Epimentioning
confidence: 99%
“…First, we show EPI's ability to handle biologically realistic circuit models using a five-neuron model of the stomatogastric ganglion [41]: a neural circuit whose parametric degeneracy is closely studied [42]. Then, we show EPI's scalability to high dimensional parameter distributions by inferring connectivities of recurrent neural networks that exhibit stable, yet amplified responses -a hallmark of neural responses throughout the brain [43][44][45]. In a model of primary visual cortex [46,47], EPI reveals how the recurrent processing across different neuron-type populations shapes excitatory variability: a finding that we show is analytically intractable.…”
Section: Introductionmentioning
confidence: 99%